Core–shell magnetic nanoparticles display synergistic antibacterial effects against Pseudomonas aeruginosa and Staphylococcus aureus when combined with cathelicidin LL-37 or selected ceragenins - Niemirowicz, Katarzyna (Int J Nanomedicine, 2016)
Core–shell magnetic nanoparticles (MNPs) are promising candidates in the development of new treatment methods against infections, including those caused by antibiotic-resistant pathogens. In this study, the bactericidal activity of human antibacterial peptide cathelicidin LL-37, synthetic ceragenins CSA-13 and CSA-131, and classical antibiotics vancomycin and colistin, against methicillin-resistant Staphylococcus aureus Xen 30 and Pseudomonas aeruginosa Xen 5, was assessed alone and in combination with core–shell MNPs. Fractional inhibitory concentration index and fractional bactericidal concentration index were determined by microdilution methods. The potential of combined therapy using nanomaterials and selected antibiotics was confirmed using chemiluminescence measurements. Additionally, the ability of tested agents to prevent bacterial biofilm formation was evaluated using crystal violet staining. In most conditions, synergistic or additive effects were observed when combinations of core–shell MNPs with ceragenins or classical antibiotics were used. Our study revealed that a mixture of membrane-active agents such as LL-37 peptide or ceragenin CSA-13 with MNPs potentialized their antibacterial properties and might be considered as a method of delaying and overcoming bacterial drug resistance.